Penggunaan Kembali Istilah Organisasi Papua Merdeka (OPM) Oleh TNI: Analisis Alasan dan Hubungannya dengan Prinsip Negara Hukum - Yuliana Rahmi Salsabila; Rahmawati Ramadhani; Lostauli Pane (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this article is to explore the reasons behind the TNI's change of name from KST or KKB to OPM, as well as the relevant principles of the rule of law. The TNI Commander issued a decree on this matter based on acts of terror and violations of human rights committed by the group in the Papua region, which have threatened national security. One of the principles of the rule of law owned by the State of Indonesia is the guarantee of human rights by law. The Indonesian government wants to resolve this conflict not only through a military approach, but also with economic, educational, health, and political approaches. The name change has raised public concerns about an increase in military operations that could harm civilians because there is no guarantee of protection from weapons activities that might occur. In addition, this name change is only carried out by the TNI alone and needs support from many parties.